Relationships of language learning variables in the acquisition of third languages in a multilingual context - Jeffrey Dawala Wilang; Thanh Vo Duy (International Journal of Evaluation and Research in Education (IJERE), 2021)
This paper reinforces the importance of third language acquisition research in a multilingual context focusing on language experience, vocabulary learning strategies, emotional self-regulation strategies, and language anxiety. This study explored three languages: Chinese, Korean, and Vietnamese, to know if there are significant relationships between the above variables in third language acquisition. Three specific sets of survey questionnaires were distributed to various students enrolled in foreign language courses offered in a language department in a university. To focus on the relationships of language learning variables of a foreign language, correlational design was used to analyze the survey questionnaires' responses for each language course. Among students who were enrolled in Chinese, significant relationships were established between language anxiety and language experience, language anxiety, and emotional self-regulation strategies. Significant associations were found between emotional self-regulation strategies and language experience, emotional self-regulation strategies, and vocabulary strategies, and language performance and language experience for those students enrolled in the Korean language. In learning Vietnamese, significant relationships were found between language anxiety and vocabulary strategies, language performance, and language anxiety. Teachers may need to re-evaluate prepared teaching and learning materials, for example, material difficulty, to help students alleviate anxiety in learning.